2013
DOI: 10.1051/0004-6361/201220190
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength interferometric observations and modeling of circumstellar disks

Abstract: Aims. We investigate the structure of the innermost region of three circumstellar disks around pre-main sequence stars HD 142666, AS 205 N, and AS 205 S. We determine the inner radii of the dust disks and, in particular, search for transition objects where dust has been depleted and inner disk gaps have formed at radii of a few tenths of AU up to several AU. Methods. We performed interferometric observations with IOTA, AMBER, and MIDI in the infrared wavelength ranges 1.6−2.5 μm and 8−13 μm with projected base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 102 publications
4
19
0
Order By: Relevance
“…In V1026 Sco, a magnetic field has not been detected (Alecian et al 2013a), which could mean that it is weak, as expected for Herbig Ae stars (Weise et al 2010). Even if a magnetic field exists, but could not be detected, the high value of the stellar rotation velocity of V1026 Sco suggests that rotational braking via disk locking (Koenigl 1991;Stȩpień 2000) is much weaker than in T Tauri stars. PA |PA-ϑ| r Ring in = 1.30 ± 0.14 mas H band …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In V1026 Sco, a magnetic field has not been detected (Alecian et al 2013a), which could mean that it is weak, as expected for Herbig Ae stars (Weise et al 2010). Even if a magnetic field exists, but could not be detected, the high value of the stellar rotation velocity of V1026 Sco suggests that rotational braking via disk locking (Koenigl 1991;Stȩpień 2000) is much weaker than in T Tauri stars. PA |PA-ϑ| r Ring in = 1.30 ± 0.14 mas H band …”
Section: Discussionmentioning
confidence: 95%
“…Monnier et al (2005) have performed Keck Interferometer (KI) measurements of V1026 Sco and found an inner disk diameter of 2.52 mas (0.29 AU at 116 pc). In a recent publication, Schegerer et al (2013) have reported mid-and near-infrared (NIR) interferometric observations (archival MIDI/VLTI & IOTA data), and performed radiative transfer modeling of V1026 Sco, and derived a disk structure with a gap from 0.35 AU to 0.80 AU.…”
Section: Introductionmentioning
confidence: 99%
“…The inset on the top right shows the observed line profile (black) and the fitted profile (blue). The vertical red line shows the inner edge of the dust disk at ∼ 1 AU as inferred from IR interferometry (Schegerer et al 2013). as the accretion rates are normal and the stellar abundances for these sources close to solar (Kama et al 2015;Banzatti et al 2018). The lower sub-mm intensity implies a lower dust surface density at 1 AU.…”
Section: Inner Disk Co Emission Is Confined By Substructuresmentioning
confidence: 96%
“…For at least two group II disk sources, gaps have already been claimed. Based on near-and mid-infrared interferometric observations (IOTA and MIDI, respectively) Schegerer et al (2013) modeled the disk around HD 142666 as having a gap with a radius of 0.8 au, plus an additional inner disk between 0.3 and 0.35 au. Chen et al (2012), on the other hand, observed and analyzed the disk around HD 144432, and their interferometric observations (AMBER and MIDI) point to a similar model with a gap radius of 1 au and a compact 0.2-au radius inner ring.…”
Section: Overlap In Spatial Properties Group I and Iimentioning
confidence: 99%